Assessing the Policy Landscape for Salt Reduction in South-East Asian and Latin American Countries – An Initiative Towards Developing an Easily Accessible, Integrated, Searchable Online Repository. Issue 1 (15th July 2021) - Kaushik, Aprajita; Peralta-Alvarez, Frank; Gupta, Priti; Bazo-Alvarez, Juan Carlos; Ofori, Sandra; Bobrow, Kirsty; Monyeki, Dan; Guinto, Renzo R.; Baumgartner, Jill; Mohan, Sailesh
Background: High dietary salt intake is an avoidable cause of hypertension and associated cardiovascular diseases (CVDs). Thus, salt reduction is recommended as one of the most cost-effective interventions for CVD prevention and for achieving the World Health Organization's (WHO) 25% reduction in premature non-communicable disease (NCD) mortality by 2025. However, current and comprehensive information about national salt reduction policies and related actions across different regions are difficult to access and impede progress and monitoring. Objectives: As an initial step to developing an online repository of salt reduction policies and related actions, and to track nation-wise progress towards the WHO's 25 by 25 goal, we aimed to identify and assess salt reduction policies and actions in select countries from two of the top five most populous regions of the world- the South-East Asia and Latin America. Methods: We conducted a literature review to identify national and regional salt reduction policies in the selected South-East Asian and Latin American countries, from January 1990–August 2020, available in English and Spanish. We also contacted selected WHO country offices (South-East Asian region) or relevant national authorities (Latin America) to gain access to unpublished documents. Results: In both regions, we found only a few dedicated stand-alone salt reduction policies: Bhutan, Sri-Lanka and Thailand from South East Asia and Costa Rica from Latin America. Available polices were either embedded in other national health/nutritional policy documents/overall NCD policies or were unpublished and had to be accessed via personal communication. Conclusions: Salt reduction policies are limited and often embedded with other policies which may impede their implementation and utility for tracking national and international progress towards the global salt reduction target associated with the 25 by 25 goal. Developing an online repository could help countries address this gap and assist researchers/policymakers to monitor national progress towards achieving the salt reduction target.